The cost-effectiveness of an additional surgical scrub in reducing prosthetic joint infections in total hip and knee arthroplasty - Tye, Cooper; Lawand, Jad; Moretti, Vincent (International Journal of Research in Orthopaedics, 2024)
Background: Surgical skin preparation prior to total knee and hip arthroplasty is an important step in infection prevention. Compared to a single application, repeat skin preparation after draping demonstrates greater efficacy in reducing the overall occurrence of surgical site infections in total joint arthroplasty. We sought to find if the addition of an extra surgical scrub after draping is a cost-effective means of decreasing prosthetic joint infection (PJI), and if so, under what conditions it would be most cost-effective. Methods: We employed a model to assess the cost-effectiveness of repeat skin preparation in total knee and hip arthroplasty. This model determines a threshold at which the expenses associated with a new intervention is offset by its ability to reduce overall costs. Literature review and records from our institution were used to draw average expenses for treatment of PJI, as well as surgical prep scrubs, to evaluate at their cost-effectiveness. We also compared against hypothetical higher and lower costs and infection rates to gain further information on the additional surgical prep’s cost-effectiveness. Results: Each of the surgical scrubs is cost-effective at our institution's cost when an absolute risk reduction (ARR) of 0.01% is achieved. The cost-effectiveness was also noted with hypothetically higher infection rates and scrub cost prices. Lower potential two-stage revision costs make the additional surgical scrub less cost-effective. Conclusions: Our findings demonstrate that an extra surgical scrub can be cost-effective way of decreasing PJI across a variety of different surgical scrub prices, arthroplasty revision costs, and PJI rates.